Improving the Scientific Argumentation Skills of Physical Education Students Through the Argument Driven Inquiry Learning Model - Dian Pujianto; Yahya Eko Nopiyanto; Syafrial; Bayu Insanistyo (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2023)
Improving scientific argumentation skills through the application of the ADI learning model is the main goal of this research. Classroom action research through cycle 1 and cycle 2 was applied to achieve the research objectives. The procedure in this study consisted of five stages, namely: planning, implementing actions, observing, and reflecting. A total of 50 students were involved as subjects in this classroom action research. The subjects are physical education students in the fifth semester who are taking research methodology lectures. Data collection was carried out in 2 cycles, the first cycle was carried out in August- October 2022. Data collection techniques and instruments in this classroom action research were used techniques such as observation, argumentation ability test, and interviews. From the results of the analysis of observational data, it is known that in cycle 1 there is an average value of 70.67% and in cycle 2 it increases to 84%. Scientific argumentation skills in cycle 1 are 68.4% and in cycle 2 are 82%. In cycle 1, it is known that student learning completeness is 72%, while in cycle 2, student learning completeness is 82%. So it can be concluded that applying the ADI learning model can improve the scientific argumentation skills of physical education students.